Implications of Budget Transparency on Public Trust in Management Budget in Government: A Systematic Literature Review - Pratiwi, Nathania; Haliah, Haliah; Kusumawati, Andi (Transpublika Publisher, 2025)
This study examines the implications of budget transparency on public trust in government budget management. This study uses the Systematic Literature Review (SLR) approach by reviewing relevant articles from various sources, such as ResearchGate, OpenKnowledge, and the Publish and Perish application. The results show that budget transparency has a positive and significant impact on public trust, increases accountability, reduces information gaps, and strengthens the government's image. Public participation in the budget process, supported by easy access to budget information, also plays an important role. In addition, open government data transparency (OGD) and participatory budgeting were identified as effective ways to increase public trust. The study also highlights obstacles to the implementation of budget transparency, such as the lack of formal structures in civil society and the lack of community involvement as equal partners. In conclusion, the government needs to continue to improve budget transparency, expand access to information, and strengthen the role of civil society to build public trust and government legitimacy.